BINA PARTISIPASI KELUARGA (BPK) PADA PENATALAKSANAAN KEJADIAN STUNTING USIA PRESCHOOL DI ERA PANDEMI COVID-19 - Elfina Natalia; Maria Floriana Ping (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
The role of the family structure is very important in maintaining the health of family members, especially children, in this case in the handling and prevention of stunting at preschool age in the COVID-19 pandemic era. The purpose of this study was to determine the implications of Bina Partisipasi Keluarga (BPK) on the handling and prevention of stunting at preschool age. This is a quantitative study using a quasi-experimental method with a non-equivalent control group design. The sample is the mothers of parents of preschool age children with a total of 20 people, which are divided into the intervention group (IG) and the control group (CG) with 10 respondents each. The results showed that there was a significant difference between knowledge (p = 0.000) and mother's attitude in providing nutrition to children, before and after the of Bina Partisipasi Keluarga (BPK) intervention (p = 0.046) in IG, while in CG there was no significant difference. on knowledge (pv=0.655) and attitude (pv=1,000). The BPK program is very important to do in order to increase the knowledge and attitudes of mothers in the management and prevention of stunting in preschool age children.